FAKTOR PENYEBAB IBU HAMIL TIDAK PATUH DALAM KONSUMSI TABLET FE - Nursiah, Andi; Noviana, Ekki; Hasnia, Hasnia; Apsari, Duhita Dyah (Ensiklopedia of Journal, 2025)
Anemia is one of the most common global health problems, affecting an estimated 500 million people worldwide. Regular administration of iron (Fe) tablets is one of the main strategies in the prevention and treatment of anemia. The purpose of this study was to determine the factors causing pregnant women to be non-compliant in taking Fe tablets. A cross-sectional study design was used in this study. The study was conducted at the Dau Community Health Center in September 2024. The population consisted of pregnant women in their second and third trimesters who visited the health center for check-ups. The sample consisted of 67 respondents. Purposive sampling was used to select the sample. The research instrument was a questionnaire. Data analysis was performed using univariate and bivariate methods. The results showed a relationship between knowledge (p value: 0.039) and no relationship between service satisfaction (p value: 0.256) and compliance with iron tablet consumption. It is recommended that health centers provide continuous education and consultation when examining the condition of pregnant women so that they understand the importance of iron tablets for the health of pregnant women. Keywords: Anemia, Knowledge, Iron Tablets